ANALYSIS OF FREE AND BOUND MORPHEME IN LYRICS OF ED SHEERAN SONG PERFECT - Atigo Alam Chayo; Hanif Maulaniam Sholah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Language can be a tool to communicate with each other in life, language can make individuals relate to each other. The objective of this research is to find out free morpheme and bound morpheme in the "Perfect" song from Ed Sheeran. In this study, the results are describes use a descriptive qualitative method. A single English song serves as a data source. Data are analyzed using data reduction, submission, and completion. This study aims to examine free morphemes and morpheme associated with the lyrics of Ed Sheeran's song "Perfect". In the results of this study, the overall results of free and bound morphemes were 159 data. With the amount of free morpheme data division found as much as 130 data (81.76%) and the amount of bound morpheme data as much as 29 data (18.24%). The results of this study can be an example and also a reference for students who want to know more about learning free and bound morphemes.